Qur’anic Analysis of Gamelan Singo Mengkok and Tembang Pangkur as Sunan Drajat’s Cultural Dakwah - Azhari Falakhuddin Al-Hafidz; Estalia Rona Ratu Roy; Yandri Agusta Putra; Yandra Agusta Putra; Ahmad Fadhol Maulana (UIN Maulana Malik Ibrahim Malang, 2026)
This study examines the role of Gamelan Singo Mengkok and Tembang Pangkur as cultural daʿwah media used by Raden Qasim (Sunan Drajat) to spread Islam along Java's northern coast during the 15th–16th centuries. While research on the Walisongo is widespread, few studies integratively analyze the symbolic meaning of Singo Mengkok and the textual message of Pangkur through a Qur’anic perspective, leaving a critical gap in understanding how art, scripture, and daʿwah values interconnect. This study explores how these traditional art forms functioned as persuasive media for conveying moral, spiritual, and social teachings, and identifies the specific Qur’anic values embedded within them. Employing a descriptive qualitative method with a historical-analytical and interpretive approach, the research draws on primary sources—including Tembang Pangkur lyrics, field observations at the Sunan Drajat Museum, and custodian interviews—alongside secondary literature on Javanese culture and Qur’anic studies. The findings reveal that Gamelan Singo Mengkok symbolizes humility and self-control, serving as an effective tool for daʿwah bil-hikmah (wise propagation). Meanwhile, Tembang Pangkur conveys core values of monotheism, repentance, obedience, knowledge-seeking, social responsibility, and national unity. These elements align with Qur’anic principles of wisdom and cultural accommodation, allowing Islamic teachings to integrate harmoniously with local traditions. In conclusion, the synthesis of Gamelan Singo Mengkok and Tembang Pangkur represents a transformative daʿwah model relevant for addressing contemporary moral, spiritual, and social challenges. Future research should leverage digital humanities to preserve and adapt these traditional arts through modern technology. Penelitian ini mengkaji peran Gamelan Singo Mengkok dan Tembang Pangkur sebagai media dakwah kultural yang digunakan oleh Raden Qasim (Sunan Drajat) untuk menyebarkan Islam di sepanjang pantai utara Jawa pada abad ke-15 hingga ke-16. Meskipun penelitian tentang Walisongo sudah meluas, belum banyak studi yang menganalisis secara integratif makna simbolis Singo Mengkok dan pesan tekstual Pangkur melalui perspektif Al-Qur'an. Hal ini menyisakan celah kritis dalam memahami bagaimana seni, kitab suci, dan nilai-nilai dakwah saling keterkaitan. Penelitian ini bertujuan untuk mengeksplorasi bagaimana bentuk-bentuk kesenian tradisional tersebut berfungsi sebagai media persuasif untuk menyampaikan ajaran moral, spiritual, dan sosial, serta mengidentifikasi nilai-nilai Al-Qur'an yang terkandung di dalamnya. Dengan menggunakan metode kualitatif deskriptif melalui pendekatan historis-analitis dan interpretatif, penelitian ini bertumpu pada sumber-sumber primer—termasuk lirik Tembang Pangkur, pengamatan lapangan di Museum Sunan Drajat, dan wawancara dengan juru kunci—serta literatur sekunder tentang kebudayaan Jawa dan studi Al-Qur'an. Hasil penelitian menunjukkan bahwa Gamelan Singo Mengkok melambangkan kerendahan hati dan pengendalian diri, yang berfungsi sebagai sarana efektif untuk dakwah bil-hikmah (penyeruan yang bijaksana). Sementara itu, Tembang Pangkur menyampaikan nilai-nilai inti berupa tauhid, pertobatan, ketaatan, pencarian ilmu, tanggung jawab sosial, dan persatuan nasional. Elemen-elemen ini selaras dengan prinsip-prinsip Al-Qur'an tentang hikmah dan akomodasi kultural, yang memungkinkan ajaran Islam berintegrasi secara harmonis dengan tradisi lokal. Kesimpulannya, sintesis antara Gamelan Singo Mengkok dan Tembang Pangkur merepresentasikan sebuah model dakwah transformatif yang relevan untuk menjawab tantangan moral, spiritual, dan sosial kontemporer. Penelitian di masa depan perlu memanfaatkan pemanfaatan humaniora digital untuk melestarikan dan mengadaptasikan kesenian tradisional berbasis dakwah ini melalui teknologi modern